2021
DOI: 10.1177/09544062211020773
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of laminar separation bubble over a supercritical airfoil in an incompressible flow

Abstract: Supercritical airfoils have an unknown behavior at incompressible flow regime and Reynolds numbers lower than those related to their design point at transonic condition. In this work, boundary layer transition is studied over a supercritical airfoil by means of hot-film and pressure measurements completed with numerical simulations. The experiments are performed at chord-based Reynolds number of [Formula: see text]and Mach number of [Formula: see text] at different angles of attack. Hot-film measurement over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…They concluded that the frequency, transition, and transition location were affected by the roughness. To predict boundary layer relaminarization, the laminar separation bubble over a supercritical airfoil was investigated numerically and experimentally by Tatar et al [ 18 ]. The transition points were observed using the second derivative of surface pressure data, hot-film measurements, and numerical transition models.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the frequency, transition, and transition location were affected by the roughness. To predict boundary layer relaminarization, the laminar separation bubble over a supercritical airfoil was investigated numerically and experimentally by Tatar et al [ 18 ]. The transition points were observed using the second derivative of surface pressure data, hot-film measurements, and numerical transition models.…”
Section: Introductionmentioning
confidence: 99%
“…With the widespread use of unmanned aerial vehicles, the flow separation control technology 10 of the subsonic airfoil has been greatly developed, and the decreased separation bubble 11 will reduce the energy consumption and improve the flight stability. Açıkel and Genç 12 researched the laminar separation bubble through force and pressure measurements, flow visualization via smoke-wire technique and velocity measurement via hot-wire system.…”
Section: Introductionmentioning
confidence: 99%